Does Physical Exercise Ameliorate Chronic Kidney Disease-Related Complications? The Case of Anaemia and Chronic Kidney Disease-Mineral Bone Disorder - Filippo Aucella; Maria Amicone; Aurora del Mar Perez Ys; Francesco Aucella; Giuseppe Gatta; Michele Antonio Prencipe; Eleonora Riccio; Ivana Capuano; Antonio Pisani; Yuri Battaglia (Karger Publishers, 2024)
Background: Physical exercise (PE) can regulate inflammation, cardiovascular health, sarcopenia, anaemia, and bone health in the chronic kidney disease (CKD) population. Experimental and clinical studies both help us better understand the mechanisms that underlie the beneficial effects of the exercise, especially in renal anaemia and CKD-mineral bone disorders (CKD-MBDs). Here, we summarize this evidence, exploring the biological pathways involved, locally released substances, and crosstalk between tissues, but also the shortcomings of current knowledge. Summary: Anaemia: Both in healthy and CKD subjects, PE may mimic hypoxia, inhibiting PHDs; so hydroxylate HIF-α subunits may be translocated into the nucleus, resulting in dimerization of HIF-1α and HIF-1β, recruitment of p300 and CBP, and ultimately, binding to HREs at target genes to cause activation. However, in CKD subjects acute PE causes higher levels of lactate, leading to iron restriction by upregulating hepatic hepcidin expression, while chronic PE allows an increased lactate clearance and HIF-α and VEGFα levels, stimulating both erythropoiesis and angiogenesis. CKD-MBD: PE may improve bone health decreasing bone resorption and increasing bone formation throughout at least three main pathways: (a) increasing osteoprotegerin and decreasing RANKL system; (b) decreasing cytokine levels; and (c) stimulating production of myokines and adipokines. Key Messages: Future research needs to be defined to develop evidence-based exercise guidance to provide optimal benefit for CKD using exercise interventions as adjuvant therapy for CKD-related complications such as anaemia and CKD-MBD.